Pengembangan Media Berbasis “Maps of Gita” Pada Materi Pecahan Untuk Siswa Kelas V SD - Hana Lestari; Ima Rahmawati; Sagita Fitriyani; Ridwan Siskandar (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to develop “Maps of Gita” learning media on grade V fraction material to help students improve their concept understanding. This research was conducted at SDN Cemplang 01 Bogor Regency and involved 58 grade V students in the 2023/2024 academic year. The research method used is a research and development model using the ADDIE model with stages: (1) Analyze, (2) Design, (3) Development, (4) Implementation, (5) Evaluation. Data were collected in various stages, namely: (1) analysis stage, need assessment and curriculum analysis; (2) design stage includes the preparation of media design, materials, and assessment instruments; (3) development stage includes making media, validation by material experts and media experts, and revision based on input through expert validation questionnaires; (4) implementation stage, involves limited trials to grade V students through pretests and postests to measure students' understanding of concepts before and after using the media; (5) evaluation stage, assessing the effectiveness of the media in improving students' understanding of fraction concepts through student response questionnaires. The results showed that the maps of gita media is feasible to use as a fraction learning media for grade V students. This media obtained a "very good" assessment from material experts (90.55%) and media experts (92.60%). The limited trial also showed that this media is effective in improving students' understanding of the concept of fractions. The pretest score of students' concept understanding was 53% and the post test was 86.33%, with an average response to the use of media of 93.33% with a very good category. Thus, "maps of gita " media can be an interesting and innovative alternative learning media to help students understand fraction material in elementary school.